Nd:YAG Adhesiolysis: A Novel Approach to Tractional Retinal Detachment From Beyond-the-Edge Proliferation After Retinectomy. (November 2018) - Chod, Ross; Landa, Gennady; Rosen, Richard
Retinectomy can be complicated by recurrent retinal elevation and subretinal fluid (SRF) accumulation secondary to tractional chorioretinal adhesion band formation and contraction. Classically, this complication requires repeat vitrectomy with destruction of adhesion bands using the vitrectomy instrument. We present a novel, nonoperative technique utilizing neodymium-yttrium-aluminum-garnet (Nd:YAG) laser to address tractional retinal elevation of a retinectomy edge causing SRF accumulation secondary to peripheral chorioretinal adhesion formation after retinectomy. Nd:YAG laser was used to perform targeted adhesiolysis to release the tractional forces on the retina, after which argon laser retinopexy was performed. Retinal reattachment with resolution of SRF was achieved without the need for reoperation.